2018
DOI: 10.1186/s12885-017-3796-1
|View full text |Cite
|
Sign up to set email alerts
|

A modified TNM staging system for non-metastatic colorectal cancer based on nomogram analysis of SEER database

Abstract: Background: To revise the American Joint Committee on Cancer TNM staging system for colorectal cancer (CRC) based on a nomogram analysis of Surveillance, Epidemiology, and End Results (SEER) database, and to prove the rationality of enhancing T stage's weighting in our previously proposed T-plus staging system. Methods: Total 115,377 non-metastatic CRC patients from SEER were randomly grouped as training and testing set by ratio 1:1. The Nomo-staging system was established via three nomograms based on 1-year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
(34 reference statements)
0
38
0
Order By: Relevance
“…Although classification according to TNM and Union for International Cancer Control stage provides valuable prognostic information and guides therapy decisions, the response and outcome of individual patient’s therapy is not predicted enough. 41 Increasing evidence showed that the circRNAs could be prognostic markers for cancers, including CRC. 42 In our study, log-rank test showed that low expression level of hsa_circ_0000711 was significantly associated with poor OS of CRC patients, which was in accordance with our univariate Cox proportional hazards analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Although classification according to TNM and Union for International Cancer Control stage provides valuable prognostic information and guides therapy decisions, the response and outcome of individual patient’s therapy is not predicted enough. 41 Increasing evidence showed that the circRNAs could be prognostic markers for cancers, including CRC. 42 In our study, log-rank test showed that low expression level of hsa_circ_0000711 was significantly associated with poor OS of CRC patients, which was in accordance with our univariate Cox proportional hazards analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some attempts to modify this classification to improve patients’ outcomes, particularly in early-stage non-metastatic cancer, where more emphasis is placed on the importance of T category [9]. There is evidence from cancer registry analysis that enhanced weighting of T category in early-stage colon cancer patients may provide clinicians with an improved system of classifying colon tumours [10]. However, as the increasing need for personalized medicine and enhanced models of risk in cancer patients that can be adopted by the clinical community is recognized [11], further studies to validate this approach will be required.…”
Section: For Colon Cancer Grading and Staging Is The Current Classifmentioning
confidence: 99%
“…However, the current AJCC prognostic guidelines that use the tumor, lymph node, and metastasis (TNM) status for PDAC do not include other possible variables that affect patient prognosis following surgery. Therefore, more accurate disease-specific predictive models are still required for patients with PDAC of the head of the pancreas who undergo radical surgery with pancreaticoduodenectomy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram is a simple multivariate predictive model, which can incorporate several variables that influence disease prognosis [ 3 ]. Recently, disease-specific nomograms have been increasingly used to predict prognosis for patients with a variety of malignant tumors [ 2 , 4 8 ]. However, there have been few studies on the use of nomograms in pancreatic ductal adenocarcinoma, and the models that have been developed have shown limited predictive ability [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%